Antioxidant Activity and Essential Amino acid Content of Bread Wheat (Triticum aestivum L.) Varieties - Osman Erekul; Ali Yiğit (Journal of Agricultural Sciences)
In recent years, consumption of healthy and nutritious products has come to the forefront with the increased consumers’ awareness because of sensitivity to human health. Bread wheat provides the important proportion of protein, fiber, mineral, and antioxidant compounds that detected wheat and wheat-based products in daily consumption. The study aimed to provide new insights and results on the antioxidant properties and essential amino acid profile of 45 bread wheat varieties collected from different ecological regions of Turkey. Antioxidant activity was measured using DPPH radical and total phenolic content was determined by using the Folin-Ciocalteu method used gallic acid as standard. Essential amino acid content was evaluated by oxidation and hydrolysis procedure by HPLC analysis. As a result of the study, significant differences and correlations were found between the varieties and all evaluated parameters. Total phenolic content and antioxidant activity values respectively ranged between 102.4 and 211.8 μg GAE/g (gallic acid equivalent/g), 11.8 and 26.3% inhibition in whole wheat flour. Amino acid amount and profile were significantly affected by variety and the most limiting amino acid lysine showed a wide range (0.39-1.47 g/100 g flour) and the concentration of leucine and phenylalanine were found to be higher in wheat compared to the other essential amino acids. Correlation analysis between protein and essential amino acids demonstrated a positive correlation with high values. Clustering analysis highlighted an important genetic diversity, suggesting that winter growth habit varieties have valuable nourishment properties with high protein and amino acid composition. These data suggest that health and nourishment properties influenced differently by genotype potential of wheat grain.